Question: Show that z p pq
Show that z = - p / √pq / n can be derived from z = X - µ / σ by substituting µ = np and σ = √npq and dividing both numerator and denominator by n.
Relevant QuestionsA recent survey found that 68.6% of the population own their homes. In a random sample of 150 heads of households, 92 responded that they owned their homes. At the α = 0.01 level of significance, does that suggest a ...Using Table G, find the critical value(s) for each, show the critical and noncritical regions, and state the appropriate null and alternative hypotheses. Use σ2 = 225. a. α = 0.05, n = 18, right-tailed b. α = 0.10, n = ...Using Table G, find the P-value interval for each x2 test value. a. x2 = 29.321, n = 16, right-tailed b. x2 = 10.215, n = 25, left-tailed c. x2 = 24.672, n = 11, two-tailed d. x2 = 23.722, n = 9, right-tailed e. x2 = 13.974, ...The average weekly earnings in the leisure and hospitality industry group for a recent year was $273. A random sample of 40 workers showed weekly average earnings of $285 with the population standard deviation equal to 58. ...An MP3 manufacturer claims that 65% of teenagers 13 to 16 years old have their own MP3 player. A researcher wishes to test the claim and selects a random sample of 80 teenagers. She finds that 57 have their own MP3 players. ...
Post your question